EMMPRIN AND HUMAN β-DEFENSIN-3 - BIOMARKER MOLECULES IN PREMALIGNANT ORAL LESIONS: CORRELATIVE IMMUNOHISTOCHEMICAL STUDY - Doinița Temelie-Olinici; Ana-Emanuela Botez; Oana-Mihaela; Carmen Solcan; Vasile Bogdan Grecu; Laura Stoica; Pavel Onofrei; Carmen Elena Cotrutz (Romanian Society of Oral Rehabilitation, 2021)
Aim of the study The current pandemic context, with a significant negative impact on the oral mucosa pathology, requires intensified research on the risk of malignant transformation of the most common premalignant oral lesions, precursors of oral squamous cell carcinoma. The present study aimed to evaluate some of the latest checkpoints of oral carcinogenesis, represented by EMMPRIN and human β-defensin-3 beta, with a vital role in tumour microenvironment. Materials and methods Fragments of oral mucosa were collected from 40 patients clinically and histopathological diagnosed with leukoplakia and erosive lichen planus to perform the immunohistochemical technique using the NovoLinkTM Max Polymer Detection System kit. Results The intensely positive immunoreactivity of the studied molecules, both at the membrane and cyto-plasmic level, correlates directly proportionally with the risk of malignant transformation. Conclusions The obtained results indicated the importance of molecular diagnosis in building a targeted and personalized therapeutic strategy, the modern medicine desideratum.